2000
DOI: 10.1074/jbc.m002077200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Function of Phosphoinositide 3-Kinase in T Cell Ca2+ Signaling

Abstract: This study presents evidence that phosphoinositide (PI) 3-kinase is involved in T cell Ca 2؉ signaling via a phosphatidylinositol 3,4,5-trisphosphate PI(3,4,5)P 3 -sensitive Ca 2؉ entry pathway. First, exogenous PI(3,4,5)P 3 at concentrations close to its physiological levels induces Ca 2؉ influx in T cells, whereas PI(3,4)P 2 , PI(4,5)P 2 , and PI(3)P have no effect on [ entry. This PI(3,4,5)P 3 -stimulated Ca 2؉ influx connotes physiological significance, considering the pivotal role of PI 3-kinase in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…It is noteworthy that the proposed involvement of PI3K in the regulation of a non-capacitative Ca 2ϩ influx pathway is reminiscent of our finding of a PI(3,4,5)P 3 -sensitive Ca 2ϩ entry mechanism in platelets (19) and Jurkat T cells (20). Consequently, we hypothesize that this PI (3,4,5 …”
mentioning
confidence: 62%
See 2 more Smart Citations
“…It is noteworthy that the proposed involvement of PI3K in the regulation of a non-capacitative Ca 2ϩ influx pathway is reminiscent of our finding of a PI(3,4,5)P 3 -sensitive Ca 2ϩ entry mechanism in platelets (19) and Jurkat T cells (20). Consequently, we hypothesize that this PI (3,4,5 …”
mentioning
confidence: 62%
“…The identity and purity of all inositol phosphates and inositol lipids were verified by 1 H and 31 P NMR and high resolution mass spectrometry. Published data from this and other laboratories have shown that PI(3,4,5)P 3 and other inositol lipids are cell-permeant and can readily fuse with cell membranes to exert cellular responses in different types of cells, including platelets (19), NIH3T3 cells (23), adipocytes (24), and Jurkat T cells (20). Fura-2 acetoxymethyl ester (fura-2 AM), fluo-3 acetoxymethyl ester (fluo-3 AM), and 2-aminoethyoxy diphenylborate (2-APB) were purchased from Calbiochem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported recently that the phosphatidylinositol 3-kinase (PI3K)͞Akt pathway could be involved also in the IFN-␥-induced phosphorylation of Stat1 S727 in human tumor cell lines or mouse embryonic fibroblasts (15). PI3K has been shown to facilitate antigen-stimulated Ca 2ϩ flux in Jurkat T cells and mast cells (44,45), which could result in activation of Ca 2ϩ -dependent serine kinases. It seems likely that in different cellular contexts, more than one serine kinase pathway can converge on Stat1 during or after its activation through tyrosine phosphorylation on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that PI3K may alter the activity of one or more of the transport proteins that comprise the Cl Ϫ secretory machinery, and in this regard PI3K has been shown to alter ion channel activity in some cell types (48,49). However, previous studies from our laboratory suggest an inhibitory effect of PI3K on intestinal epithelial K ϩ channels (50), an effect that does not explain our current data because inhibition of K ϩ channel function would likely lead to attenuation of Cl Ϫ secretory responses (2).…”
Section: Discussionmentioning
confidence: 99%